2022
DOI: 10.1155/2022/5720875
|View full text |Cite|
|
Sign up to set email alerts
|

Thyroid Hormone Changes in the Northern Area of Tianjin during the COVID-19 Pandemic

Abstract: Purpose. This study aimed to determine whether and how stress-induced thyroid hormone changes occur during the COVID-19 pandemic in the northern area of Tianjin. Methods. This study comprised two groups of study subjects in Tianjin: before (2019) and during (2020) the COVID-19 outbreak. Subjects were included if they had FT3, FT4, and TSH concentrations and thyroid TPOAb or TgAb information available. People who were pregnant, were lactating, or had mental illness were excluded. We used propensity score matchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Immunoassays for thyroxine can be affected by alterations in serum binding protein that occurs in various physiological states (20). Decreased TSH and increased FT4 levels were reported in the healthy cohort during the COVID-19 outbreak (67). During the pandemic, relationships were found between thyroid diseases and psychiatric factors, such as anxiety and depression (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Immunoassays for thyroxine can be affected by alterations in serum binding protein that occurs in various physiological states (20). Decreased TSH and increased FT4 levels were reported in the healthy cohort during the COVID-19 outbreak (67). During the pandemic, relationships were found between thyroid diseases and psychiatric factors, such as anxiety and depression (68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women in their first trimester in Shanghai during the COVID-19 outbreak were at an increased risk of having higher FT3 concentrations, lower FT4 concentrations, and isolated hypothyroxinemia ( Lin et al, 2020 ). People in the northern area of Tianjin during the COVID-19 outbreak were at an increased risk of higher FT4, lower FT3, and lower TSH ( Weiwei et al, 2022 ). A large number of studies had shown that negative psychological status was closely related to the occurrence and development of thyroid nodules, but the association between psychological status and ultrasonic manifestations of thyroid nodules had not been analyzed ( Mizokami et al, 2004 ; Jonsdottir and Sjörs, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions based on lifestyle modifications are integral to the management of body weight [ 32 ]. It is possible that the sudden outbreak of the epidemic and local policies had a certain impact on the activities and emotions of patients and may even have affected thyroid function [ 33 ]. In our study, we also found that the quality of sleep had deteriorated in patients during the outbreak.…”
Section: Discussionmentioning
confidence: 99%